SME internationalization modes in the German biotechnology industry: The influence of imitation, network position, and international experience - Oehme, Marie; Bort, Suleika (Journal of International Business Studies, 2015)
In this article we reveal how network-enabled imitation processes impact young small- and medium-sized enterprises (SMEs) internationalization, and how a firm’s network position as well as its experiential knowledge moderate imitative behavior in internationalization modes. Building on institutional, network, and organizational-learning theory, we suggest that firms imitate the internationalization modes of their peers in their network. Moreover, we argue that a firm’s imitation propensity depends on two important boundary conditions: network position and past experience. Applying a longitudinal event history analysis to analyze the complete population of 977 German biotechnology firms between 1996 and 2012 largely supports our hypotheses. Our findings reveal that firms imitate the internationalization modes of their peers in a precise manner. This implies that the imitation of others can initially serve as a presumably convenient low-risk shortcut to a planned or experience-driven internationalization process. Furthermore, our results confirm that this imitation process is channeled through formal network relations and that central network positions that are associated with superior information access, enhanced legitimacy, and status may promote deviating behavior. Acknowledging the interplay of different learning sources, our findings additionally show that initial internationalization mode choices of SMEs can have a lasting effect on subsequent internationalization behavior. Overall, our study contributes to a more nuanced view of imitative behavior of internationalizing SMEs and its boundary conditions, and highlights future research opportunities that exist for considering imitation and its implications in international business research.